RELATIONSHIP BETWEEN HUSBAND SUPPORT AND PREGNANCY CONTROL IN PREGNANT WOMEN SUKAWENING PUSKESMAS GARUT - Lilis Mamuroh; Sukmawati .; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Data from the Garut District Health Office in 2016 showed that the number of pregnant women was 62,514. 62,818 pregnant women had 1 pregnancy check-up (K1), and only 58,594 pregnant women had 4 pregnancy check-up (K4) (Garut District Health Profile 2016). In the Health profile of Garut Regency, K4 coverage in the Sukawening Health Center area was 92.3%, public health center in Garut with the lowest K4 coverage, and 40% of pregnant women coming to health services alone, not accompanied by their husbands. Husband's support is one of the reinforcing factors and influences the pregnancy process, but information about the husband's support and its relationship with pregnancy control is still limited. The aim of the study was to determine the relationship of the husband's support to pregnant women with antenatal care (ANC) visits at Sukawening Health Center in 2016. The research method used in this study was descriptive correlational using a cross-sectional approach. Samples were selected using purposive sampling technique, 75 pregnant women were the respondents. Data collection used primary and secondary data with a measuring instrument was a note in the KIA book to find out the ANC frequency, and for husband's support used a questionnaire. Analysis of univariate data in the form of percentage and bivariate analysis with the chi-square test. The results showed that husband's support was 66.7% support and antenatal care visits were 60% completed. The analysis result of the relationship between the husband's support to pregnant women with antenatal care visits (ANC) obtained p-value = 0.012 and OR = 3.5. The conclusion is that there is a significant relationship between the husband's support for pregnant women and antenatal care (ANC) visits. Suggestions, health workers at Sukawening Health Center improve health services, especially antenatal care and involve husbands at each visit.Keywords: Antenatal care, husband’s support, ANC visit.